Toward Energy-Efficient Wastewater Regeneration: A Novel Uva-Led Photoreactor for Sulfamethoxazole Removal Via Fe3+-Edds Mediated Photo-Fenton Process - Vidal-Fuentes, J; Vidal-Fuentes, J (Elsevier Ltd, 2025)
This study presents a novel pilot-scale UVA-LED photoreactor, validated for the removal of sulfamethoxazole (SMX) from municipal wastewater via Fe3+-EDDS-mediated photo-Fenton. The effects of UVA-LED power (5–100 %) and pH (unmodified and 6) on SMX degradation were evaluated in terms of energy efficiency and economic viability, using both simulated and real secondary effluents from municipal wastewater treatment plants. In real wastewater, 75 % UVA-LED power achieved 80 % SMX removal in just 15 min. However, increasing the power to 100 % led to lower removal efficiency (65 % SMX) due to accelerated depletion of the Fe3+-EDDS complex. Notably, the system achieved an electrical energy per order (EEO) below 0.15 kWh/m3 order, confirming its competitiveness compared to conventional advanced oxidation processes, which typically range from 2 to 10 kWh/m3 order. EEO values were significantly higher in real wastewater than in simulated effluent, emphasizing the need for process optimization or integration of pre-treatments (e.g., adsorption) to enhance performance. The process also reduced chronic toxicity (Selenastrum capricornutum) with the greatest reduction at 75 % power. Techno-economic analysis showed that despite higher energy input, increased power reduced treatment time and total cost from 0.53 to 0.61 €/m3 to 0.29–0.30 €/m3. These results validate the UVA-LED photoreactor as a sustainable, energy-efficient, and cost-effective technology for municipal wastewater treatment. © 2025 The Authors